2006 8th International Conference on Solid-State and Integrated Circuit Technology Proceedings 2006
DOI: 10.1109/icsict.2006.306165
|View full text |Cite
|
Sign up to set email alerts
|

Effect of implanting silicon in buried oxide on the radiation hardness of the partially-depleted CMOS/SOI

Abstract: In order to improve the total dose radiation hardness of the buried oxides(BOX) of separation by implanted oxygen(SIMOX) silicon on insulator (SOI),we implanted silicon into the BOX at a dose of 1×1015cm-2 and then annealed at 800 in N2 ambience. Partially depleted CMOS/SOI inverters with enclosed-gate structure fabricated on improved SIMOX substrate and standard SIMOX substrate were exposed to 60Co -ray radiation. The results of demonstrate that compare to standard CMOS/SOI inverters; the improved CMOS/SOI in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2008
2008
2008
2008

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…We have recently reported that partially depleted SOI MOS transistors, fabricated in a standard 3 µm SOI CMOS (Complementary MOS) process, could achieve radiation hard performance by hardening the buried oxide and prevent back channel conduction in very harsh radiation environment [2][3][4] . We have been pursuing aggressively the development of radiation hard SOI CMOS device structures for designing radiation hard circuits to meet challenges in the near future space application.…”
Section: Introductionmentioning
confidence: 99%
“…We have recently reported that partially depleted SOI MOS transistors, fabricated in a standard 3 µm SOI CMOS (Complementary MOS) process, could achieve radiation hard performance by hardening the buried oxide and prevent back channel conduction in very harsh radiation environment [2][3][4] . We have been pursuing aggressively the development of radiation hard SOI CMOS device structures for designing radiation hard circuits to meet challenges in the near future space application.…”
Section: Introductionmentioning
confidence: 99%